The Sound of the kiss, or, the story that must never be told : Piṅgaḷi Sūrana's Kaḷāpūrṇodayamu - Piṅgaḷi Sūrana (Columbia University Press, 2002)
In this sixteenth-century masterpiece of Telugu literature, from the region now known as Andhra Pradesh, Suranna recounts the story of a young courtesan who falls in love with the most handsome man in the universe and overhears him speaking of a mysterious person whose story must never be told. Burning with curiosity and desire, she ventures to the god Krishna's palace, where much intrigue and adventure ensue. The Sound of the Kiss is considered by some to be the first novel written in South Asia, and the translation of this classic fills a gap in the literature of the East.</P.
Keywords: Love stories, South Asian -- 16th century -- Translations into English.; South Asia -- 16th century -- Translations into English.; TRAVEL -- Special Interest -- Literary.; LITERARY CRITICISM -- General.; LITERARY CRITICISM -- Asian -- Indic.; South Asia; 1500-1599; Translations